Thalidomide Alleviates Apoptosis, Oxidative Damage and Inflammation Induced by Pemphigus Vulgaris IgG in HaCat Cells and Neonatal Mice Through MyD88 - Luan C; Lu Z; Chen J; Chen M; Zhao R; Li X (Dove Medical Press, 2023)
Chunyan Luan,1,* Zhipeng Lu,2,* Juan Chen,3 Mengxing Chen,1 Ran Zhao,1 Xiaolan Li1 1Department of Dermatology, The Second Affiliated Hospital of Kunming Medical University, Kunming, People's Republic of China; 2Southwest United Graduate School, Yunnan University, Kunming, Yunnan, 650500, People's Republic of China; 3Department of Rheumatology and Immunology, The Second Affiliated Hospital of Kunming Medical University, Kunming, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaolan Li, Department of Dermatology, The Second Affiliated Hospital of Kunming Medical University, 374# Dianmian Avenue, Wuhua District, Kunming, Yunnan, People's Republic of China, Tel +86 13629684648, Email prolixl@163.comPurpose: Thalidomide (Tha) can be used as a selective treatment for mild pemphigus vulgaris (PV). However, the specific mechanism of action remains unclear.Patients and Methods: PV IgG extracted from patients' serum was cocultured with HaCaT cells to construct a PV cell model, and different concentrations of Tha were used to screen the drug effect. The expression level of MYD88 was assessed in skin lesions of PV patients. Intracellular Ca2+ concentration, reactive oxygen species level, DSG3, PG, MYD88, apoptosis-related proteins (Caspase-3, Bcl-2, and Bax), NF-κB pathway-related proteins (IκBα, p-IκBα, p50, and p65), NLRP3, IFN-γ, TNF-α, IL-6, and IL-8 levels were measured. PV IgG was subcutaneously injected into C57BL/6 neonatal mice to construct the animal model. Immunofluorescence was used to detect IgG deposition in the mouse epidermis, whereas immunohistochemistry and TUNEL methods were used to detect the expression of MYD88 and NLRP3 as well as cell apoptosis level in the mouse epidermis.Results: Tha reversed the decrease in Dsg3 and PG caused by PV IgG. The expression of MyD88 increased in the patients' skin, PV cell model, and PV mouse model. The increase in MyD88 expression level in PV cell models and PV newborn mouse models was inhibited by Tha. Overexpression of MyD88 induced a decrease in the expression levels of Dsg3 and PG in Hacat cells. Overexpression of MyD88 inhibited Tha effects on Dsg3 and PG expressions and blocked Tha effects on Ca2+, apoptosis, Bax, Bcl-2, and Caspase-3 expressions, oxidative damage, and inflammatory response in HaCat cells. Tha alleviated acantholysis induced by PV IgG in model mice.Conclusion: Through MYD88, Tha attenuated apoptosis of HaCat cells, modulated NF-κB to hamper the oxidative damage and inflammatory response in the PV cell models, and alleviated acantholysis, IgG deposition, and epidermal cell apoptosis induced by PV IgG in model mice.Keywords: pemphigus vulgaris, thalidomide, oxidative damage, apoptosis, inflammation, MyD88